Analysis of the Implementation of Discipline for State Civil Servants at the Office of Community and Village Empowerment, Pasangkayu Regency - Lukman, Andi; Rajindra, Rajindra; Rukhayati, Rukhayati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This study aimed to determine and analyze the implementation of discipline for state civil servants at the Office of Community and Village Empowerment in Pasangkayu Regency. The study results show that respondents' responses about understanding their obligations as state civil servants, who expressed doubts about one person or 3.1%, agreed with the number of 25 people or 78.1% and strongly agreed with six people or 18.8%. Respondents' responses about understanding the prohibition as state civil servants expressed doubt that one person or 3.1% agreed with the number of 20 people or 62.5% and strongly agreed with 11 people or 34.4%. And respondents' responses about punishment as state civil servants state that 19 people or 59.4% agree with the number and 13 people, or 40.6%, strongly agree.